Nitrile rubber manufacturing method
Patent Information
- Application Number
- JP2022503215
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-02-28
- Filing Date
- 2021-02-04
- Publication Date
- 2025-02-19
- Estimated Expiration
- 2041-02-04
AI Technical Summary
【0010】 本発明によれば、バレルの内部にスクリューが回転駆動自在に配置されている押出機を用いた、ニトリルゴムの製造方法において、押出機の汚れの発生および成形時に用いる金型の汚れの発生を有効に抑制可能であり、かつ、加工性に優れたニトリルゴムを製造することが可能なニトリルゴムの製造方法を提供することができる。
Smart Images

Figure 0007632450000002 
Figure 0007632450000003 
Figure 0007632450000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing nitrile rubber using an extruder in which a screw is arranged inside a barrel so as to be freely rotatable, and more specifically, to a method for producing nitrile rubber which can effectively suppress the generation of dirt in the extruder and the generation of dirt in a mold used during molding, and which can produce nitrile rubber having excellent processability. [Background technology]
[0002] Generally, to recover a polymer from a polymer latex obtained by emulsion polymerization, a coagulant such as an aqueous solution of an acid or an inorganic salt is added to the polymer latex in a coagulation tank, and the latex is coagulated while stirring. The polymer crumb obtained by this coagulation operation is then introduced into a dehydrator such as a centrifugal dehydrator or squeezer for dehydration, and then introduced into a drying device such as a band dryer, flash dryer or extrusion dryer for drying. A pelletizer or baler machine is usually connected downstream of the drying device, and the dried polymer is often finally processed into pellets, bales or sheets to be used as a product.
[0003] However, if these dehydration and drying devices are used to recover polymers from polymer latex, the number of steps increases, and the costs of the coagulation tank and auxiliary equipment become high, and the installation space required increases, which are problematic.
[0004] In order to solve such problems, for example, Patent Document 1 attempts a method in which nitrile rubber latex and a coagulant are directly fed into a screw extruder, and coagulation, dehydration, and drying are carried out inside the extruder. However, the method described in Patent Document 1 has problems such as the extruder used for coagulation, dehydration, and drying being prone to become dirty (particularly, the vent port of the extruder is prone to become dirty), resulting in insufficient productivity, and the processability of the obtained nitrile rubber being insufficient. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2011-12142 A Summary of the Invention [Problem to be solved by the invention]
[0006] The present invention has been made in consideration of the above circumstances, and has an object to provide a method for producing nitrile rubber in which nitrile rubber is recovered from nitrile rubber latex using an extruder having a screw rotatably driven inside a barrel, which can effectively suppress the generation of dirt in the extruder and the generation of dirt in a mold used during molding, and can produce nitrile rubber with excellent processability. [Means for solving the problem]
[0007] As a result of intensive research by the present inventors to achieve the above object, it was found that the above object can be achieved by continuously supplying a nitrile rubber latex and a coagulant to an extruder having a screw arranged inside a barrel that can be freely rotated, and by supplying the nitrile rubber latex to the extruder in a state in which the nitrile rubber latex contains a specific amount of a hindered phenol-based antioxidant having a molecular weight of 300 to 3000 when recovering nitrile rubber from the nitrile rubber latex, and thus completing the present invention.
[0008] That is, according to the present invention, there is provided a method for producing nitrile rubber, in which nitrile rubber is recovered from nitrile rubber latex by continuously supplying nitrile rubber latex and a coagulant to an extruder having a screw rotatably disposed inside a barrel, the method comprising the steps of: The method for producing nitrile rubber includes feeding the latex of the nitrile rubber to the extruder in a state in which the latex of the nitrile rubber contains a hindered phenol-based antioxidant having a molecular weight of 300 to 3000 in an amount of 0.1 to 3 parts by weight per 100 parts by weight of the nitrile rubber.
[0009] In the production method of the present invention, it is preferable that the maximum chemiluminescence intensity of the nitrile rubber discharged from the extruder and recovered from the nitrile rubber latex, as measured in accordance with JIS K7351:2018, is 2,000 to 25,000 counts / second. In the production method of the present invention, it is preferable that the nitrile rubber contains 5 to 60% by weight of α,β-ethylenically unsaturated nitrile monomer units and has an iodine value of 120 or less. In the production method of the present invention, it is preferable that the ratio Q / N [kg / (hr·rpm)] of the supply rate Q [kg / hr] of the nitrile rubber to the extruder to the rotation speed N [rpm] of the screw of the extruder is 0.22 kg / (hr·rpm) or less. In the production method of the present invention, when the hindered phenol-based antioxidant is added to the nitrile rubber latex, the hindered phenol-based antioxidant is preferably added in the form of an emulsion to the nitrile rubber latex. Effect of the Invention
[0010] According to the present invention, in a method for producing nitrile rubber using an extruder having a screw arranged inside a barrel that can be freely rotated, it is possible to provide a method for producing nitrile rubber that can effectively suppress the generation of dirt in the extruder and the generation of dirt in a mold used during molding, and that can produce nitrile rubber with excellent processability. [Brief description of the drawings]
[0011] [Figure 1] FIG. 1 is a schematic diagram showing an extruder used in the method for recovering nitrile rubber according to the first embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic diagram showing a screw disposed inside the extruder. [Diagram 3] FIG. 3 is a schematic, partially cut-away view of the screw of FIG. [Figure 4] 4 is a cross-sectional view taken along line IV-IV in FIG. 1 and line IV-IV in FIG. [Diagram 5] 5 is a cross-sectional view taken along line VV in FIG. 1 and line VV in FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] The method for producing nitrile rubber of the present invention comprises the steps of: A method for producing nitrile rubber, comprising the steps of continuously supplying nitrile rubber latex and a coagulant to an extruder having a screw rotatably disposed inside a barrel, and recovering nitrile rubber from the nitrile rubber latex, comprising the steps of: The nitrile rubber latex is supplied to the extruder in a state in which the nitrile rubber latex contains 0.1 to 3 parts by weight of a hindered phenol-based antioxidant having a molecular weight of 300 to 3000 per 100 parts by weight of the nitrile rubber.
[0013] <Nitrile rubber> First, the nitrile rubber used in the present invention will be described. The nitrile rubber used in the present invention is not particularly limited, but examples thereof include copolymers obtained by copolymerizing an α,β-ethylenically unsaturated nitrile monomer, a conjugated diene monomer, and other monomers copolymerizable therewith, which are used as necessary.
[0014] The α,β-ethylenically unsaturated nitrile monomer is not limited as long as it is an α,β-ethylenically unsaturated compound having a nitrile group, and examples thereof include acrylonitrile, α-halogenoacrylonitrile such as α-chloroacrylonitrile and α-bromoacrylonitrile, and α-alkylacrylonitrile such as methacrylonitrile, with acrylonitrile being preferred. The α,β-ethylenically unsaturated nitrile monomer may be used alone or in combination of two or more of these.
[0015] The content of the α,β-ethylenically unsaturated nitrile monomer unit in the nitrile rubber used in the present invention is preferably 5 to 60% by weight, more preferably 8 to 55% by weight, further preferably 10 to 50% by weight, and further more preferably 15 to 25% by weight. By setting the content of the α,β-ethylenically unsaturated nitrile monomer unit within the above range, a cross-linked rubber can be obtained that has a good balance between oil resistance and cold resistance.
[0016] As the conjugated diene monomer, a conjugated diene monomer having 4 to 6 carbon atoms such as 1,3-butadiene, isoprene, 2,3-dimethyl-1,3-butadiene, 1,3-pentadiene, chloroprene, etc. is preferred, 1,3-butadiene and isoprene are more preferred, and 1,3-butadiene is particularly preferred. These may be used alone or in combination.
[0017] The content of the conjugated diene monomer unit (including the saturated butadiene unit) in the nitrile rubber used in the present invention is preferably 10 to 89.9% by weight, more preferably 15 to 81.5% by weight, even more preferably 20 to 74% by weight, and even more preferably 32.5 to 59.5% by weight. By setting the content of the conjugated diene monomer unit within the above range, when the cross-linked rubber is produced, the rubber elasticity can be appropriately increased while the oil resistance, heat aging resistance, and chemical stability are improved.
[0018] The nitrile rubber used in the present invention is preferably one obtained by copolymerizing a carboxyl group-containing monomer in addition to an α,β-ethylenically unsaturated nitrile monomer and a conjugated diene monomer. By copolymerizing a carboxyl group-containing monomer, the compression set resistance can be improved when a cross-linked rubber is obtained.
[0019] The carboxyl group-containing monomer is not particularly limited as long as it is copolymerizable with the α,β-ethylenically unsaturated nitrile monomer and has one or more unsubstituted (free) carboxyl groups that are not esterified or the like.
[0020] Examples of the carboxyl group-containing monomer include α,β-ethylenically unsaturated monocarboxylic acid monomers, α,β-ethylenically unsaturated polycarboxylic acid monomers, and α,β-ethylenically unsaturated dicarboxylic acid monoester monomers. The carboxyl group-containing monomers also include monomers in which the carboxyl groups of these monomers form carboxylates. Furthermore, anhydrides of α,β-ethylenically unsaturated polycarboxylic acids can also be used as carboxyl group-containing monomers because they form carboxyl groups by cleaving the acid anhydride groups after copolymerization.
[0021] Examples of the α,β-ethylenically unsaturated monocarboxylic acid monomer include acrylic acid, methacrylic acid, ethylacrylic acid, crotonic acid, and cinnamic acid.
[0022] Examples of the α,β-ethylenically unsaturated polycarboxylic acid monomer include butenedioic acids such as fumaric acid and maleic acid, itaconic acid, citraconic acid, mesaconic acid, glutaconic acid, allylmalonic acid, teraconic acid, etc. Examples of the anhydrides of α,β-unsaturated polycarboxylic acids include maleic anhydride, itaconic anhydride, citraconic anhydride, etc.
[0023] Examples of the α,β-ethylenically unsaturated dicarboxylic acid monoester monomer include monoalkyl maleates such as monomethyl maleate, monoethyl maleate, monopropyl maleate, and mono-n-butyl maleate; monocycloalkyl maleates such as monocyclopentyl maleate, monocyclohexyl maleate, and monocycloheptyl maleate; monoalkyl cycloalkyl maleates such as monomethylcyclopentyl maleate and monoethylcyclohexyl maleate; monoalkyl fumarate esters such as monomethyl fumarate, monoethyl fumarate, monopropyl fumarate, and mono-n-butyl fumarate; monocycloalkyl fumarate esters such as monocyclopentyl fumarate, monocyclohexyl fumarate, and monocycloheptyl fumarate; monoalkyl cycloalkyl fumarate esters such as monomethylcyclopentyl fumarate and monoethylcyclohexyl fumarate; monoalkyl esters of citraconic acid such as monomethyl citraconic acid, monoethyl citraconic acid, monopropyl citraconic acid, and mono-n-butyl citraconic acid; monocycloalkyl esters of citraconic acid such as monocyclopentyl citraconic acid, monocyclohexyl citraconic acid, and monocycloheptyl citraconic acid; monoalkyl cycloalkyl esters of citraconic acid such as monomethylcyclopentyl citraconic acid and monoethylcyclohexyl citraconic acid; monoalkyl esters of itaconic acid such as monomethyl itaconic acid, monoethyl itaconic acid, monopropyl itaconic acid, and mono-n-butyl itaconic acid; monocycloalkyl esters of itaconic acid such as monocyclopentyl itaconic acid, monocyclohexyl itaconic acid, and monocycloheptyl itaconic acid; monoalkyl cycloalkyl esters of itaconic acid such as monomethylcyclopentyl itaconic acid and monoethylcyclohexyl itaconic acid; and the like.
[0024] The carboxyl group-containing monomer may be used alone or in combination. Among these, α,β-ethylenically unsaturated dicarboxylic acid monoester monomer is preferred, α,β-ethylenically unsaturated dicarboxylic acid monoalkyl ester monomer is more preferred, maleic acid monoalkyl ester is further preferred, and maleic acid mono-n-butyl is particularly preferred. The carbon number of the alkyl group of the alkyl ester is preferably 2 to 8.
[0025] The content of the carboxyl group-containing monomer unit in the nitrile rubber used in the present invention is preferably 0.1 to 20% by weight, more preferably 0.5 to 15% by weight, even more preferably 1 to 10% by weight, and even more preferably 2.5 to 7.5% by weight. By setting the content of the carboxyl group-containing monomer unit within the above range, the mechanical properties and compression set resistance of the obtained cross-linked rubber can be made better.
[0026] From the viewpoint of further enhancing cold resistance, the nitrile rubber used in the present invention is preferably one obtained by copolymerizing an α,β-ethylenically unsaturated nitrile monomer, a conjugated diene monomer, and a carboxyl group-containing monomer used as necessary, as well as an α,β-ethylenically unsaturated monocarboxylic acid ester monomer.
[0027] The α,β-ethylenically unsaturated monocarboxylic acid ester monomer is not particularly limited, and examples thereof include α,β-ethylenically unsaturated monocarboxylic acid alkyl ester monomer, α,β-ethylenically unsaturated monocarboxylic acid alkoxyalkyl ester monomer, α,β-ethylenically unsaturated monocarboxylic acid aminoalkyl ester monomer, α,β-ethylenically unsaturated monocarboxylic acid hydroxyalkyl ester monomer, α,β-ethylenically unsaturated monocarboxylic acid fluoroalkyl ester monomer, etc. Among these, α,β-ethylenically unsaturated monocarboxylic acid alkyl ester monomer or α,β-ethylenically unsaturated monocarboxylic acid alkoxyalkyl ester monomer is preferred.
[0028] As the alkyl ester monomer of α,β-ethylenically unsaturated monocarboxylic acid, those having an alkyl group with 3 to 10 carbon atoms as the alkyl group are preferable, those having an alkyl group with 3 to 8 carbon atoms are more preferable, and those having an alkyl group with 4 to 6 carbon atoms are even more preferable.
[0029] Specific examples of the α,β-ethylenically unsaturated monocarboxylic acid alkyl ester monomer include alkyl acrylate monomers such as methyl acrylate, ethyl acrylate, propyl acrylate, isobutyl acrylate, n-butyl acrylate, n-pentyl acrylate, 2-ethylhexyl acrylate, and n-dodecyl acrylate; cycloalkyl acrylate monomers such as cyclopentyl acrylate and cyclohexyl acrylate; alkyl acrylate cycloalkyl ester monomers such as methylcyclopentyl acrylate, ethylcyclopentyl acrylate, and methylcyclohexyl acrylate; and methacrylate monomers such as methyl methacrylate, ethyl methacrylate, propyl methacrylate, n-butyl methacrylate, n-pentyl methacrylate, and n-octyl methacrylate. acrylic acid alkyl ester monomers; methacrylic acid cycloalkyl ester monomers such as cyclopentyl methacrylate, cyclohexyl methacrylate, and cyclopentyl methacrylate; methacrylic acid alkyl cycloalkyl ester monomers such as methylcyclopentyl methacrylate, ethylcyclopentyl methacrylate, and methylcyclohexyl methacrylate; crotonic acid alkyl ester monomers such as propyl crotonate, n-butyl crotonate, and 2-ethylhexyl crotonate; crotonic acid cycloalkyl ester monomers such as cyclopentyl crotonate, cyclohexyl crotonate, and cyclooctyl crotonate; crotonic acid alkyl cycloalkyl ester monomers such as methylcyclopentyl crotonate and methylcyclohexyl crotonate; and the like.
[0030] Furthermore, as the α,β-ethylenically unsaturated monocarboxylic acid alkoxyalkyl ester monomer, those having an alkoxyalkyl group with a carbon number of 2 to 8 are preferred, those having an alkoxyalkyl group with a carbon number of 2 to 6 are more preferred, and those having an alkoxyalkyl group with a carbon number of 2 to 4 are even more preferred.
[0031] Specific examples of the α,β-ethylenically unsaturated monocarboxylic acid alkoxyalkyl ester monomer include acrylates such as methoxymethyl acrylate, methoxyethyl acrylate, methoxybutyl acrylate, ethoxymethyl acrylate, ethoxyethyl acrylate, ethoxypropyl acrylate, ethoxydodecyl acrylate, n-propoxyethyl acrylate, i-propoxyethyl acrylate, n-butoxyethyl acrylate, i-butoxyethyl acrylate, t-butoxyethyl acrylate, methoxypropyl acrylate, and methoxybutyl acrylate. Acid alkoxyalkyl ester monomers; methacrylic acid alkoxyalkyl ester monomers such as methoxymethyl methacrylate, methoxyethyl methacrylate, methoxybutyl methacrylate, ethoxymethyl methacrylate, ethoxyethyl methacrylate, ethoxypentyl methacrylate, n-propoxyethyl methacrylate, i-propoxyethyl methacrylate, n-butoxyethyl methacrylate, i-butoxyethyl methacrylate, t-butoxyethyl methacrylate, methoxypropyl methacrylate, and methoxybutyl methacrylate; and the like.
[0032] Among these α,β-ethylenically unsaturated monocarboxylic acid ester monomers, acrylic acid alkyl ester monomers and acrylic acid alkoxyalkyl ester monomers are preferred, and n-butyl acrylate and methoxyethyl acrylate are more preferred. These α,β-ethylenically unsaturated monocarboxylic acid ester monomers can also be used in combination of two or more kinds.
[0033] The α,β-ethylenically unsaturated monocarboxylic acid ester monomer may be used alone or in combination of two or more. The content of the α,β-ethylenically unsaturated monocarboxylic acid ester monomer unit in the nitrile rubber used in the present invention is preferably 5 to 60% by weight, more preferably 10 to 55% by weight, further preferably 15 to 50% by weight, and further more preferably 23 to 35% by weight. By setting the content of the α,β-ethylenically unsaturated monocarboxylic acid ester monomer unit within the above range, the cold resistance of the cross-linked rubber can be more appropriately improved.
[0034] The nitrile rubber used in the present invention may be a copolymer of the α,β-ethylenically unsaturated nitrile monomer, the conjugated diene monomer, the carboxyl group-containing monomer, and the α,β-ethylenically unsaturated monocarboxylic acid ester monomer with other monomers copolymerizable therewith. Examples of such other monomers include α,β-ethylenically unsaturated monocarboxylic acid ester monomers (excluding those mentioned above), ethylene, α-olefin monomers, aromatic vinyl monomers, fluorine-containing vinyl monomers, copolymerizable antioxidants, and the like.
[0035] Examples of the α,β-ethylenically unsaturated monocarboxylic acid ester monomer include (meth)acrylic acid esters having a cyanoalkyl group having 2 to 12 carbon atoms, such as α-cyanoethyl acrylate, α-cyanoethyl methacrylate, and cyanobutyl methacrylate; (meth)acrylic acid esters having a hydroxyalkyl group having 1 to 12 carbon atoms, such as 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, and 2-hydroxyethyl methacrylate; and (meth)acrylic acid esters having a fluoroalkyl group having 1 to 12 carbon atoms, such as trifluoroethyl acrylate and tetrafluoropropyl methacrylate.
[0036] The α-olefin monomer preferably has 3 to 12 carbon atoms, and examples thereof include propylene, 1-butene, 4-methyl-1-pentene, 1-hexene, and 1-octene.
[0037] Examples of the aromatic vinyl monomer include styrene, α-methylstyrene, and vinylpyridine.
[0038] Examples of the fluorine-containing vinyl monomer include fluoroethyl vinyl ether, fluoropropyl vinyl ether, o-trifluoromethylstyrene, vinyl pentafluorobenzoate, difluoroethylene, and tetrafluoroethylene.
[0039] Examples of the copolymerizable antioxidant include N-(4-anilinophenyl)acrylamide, N-(4-anilinophenyl)methacrylamide, N-(4-anilinophenyl)cinnamamide, N-(4-anilinophenyl)crotonamide, N-phenyl-4-(3-vinylbenzyloxy)aniline, and N-phenyl-4-(4-vinylbenzyloxy)aniline.
[0040] These copolymerizable other monomers may be used alone or in combination. The content of these other monomer units in the nitrile rubber used in the present invention is preferably 30% by weight or less, more preferably 15% by weight or less, and even more preferably 5% by weight or less.
[0041] The iodine value of the nitrile rubber used in the present invention is preferably 120 or less, more preferably 50 or less, further preferably 20 or less, and even more preferably 10 or less. By making the iodine value 120 within the above range, the heat resistance and ozone resistance of the obtained cross-linked rubber can be further improved.
[0042] The Mooney viscosity [ML1+4(100° C.)] of the nitrile rubber used in the present invention is preferably 5-200, more preferably 10-100, and further preferably 15-80.
[0043] The polymerization method for polymerizing the nitrile rubber used in the present invention is not particularly limited, and for example, a method of copolymerizing an α,β-ethylenically unsaturated nitrile monomer, a conjugated diene monomer, and a carboxyl group-containing monomer and other monomers copolymerizable therewith, which are added as necessary, is convenient and preferable. As the polymerization method, any of the known emulsion polymerization method and solution polymerization method can be used, but the emulsion polymerization method is preferable because the polymerization reaction can be easily controlled. According to the emulsion polymerization method, the nitrile rubber can be obtained in the form of a latex in which the nitrile rubber is dispersed in an aqueous medium, that is, as a latex of nitrile rubber.
[0044] In the emulsion polymerization, in addition to an emulsifier, a polymerization initiator, and a molecular weight regulator, commonly used polymerization auxiliary materials can be used.
[0045] The emulsifier is not particularly limited, but examples thereof include nonionic emulsifiers such as polyoxyethylene alkyl ethers, polyoxyethylene alkylphenol ethers, polyoxyethylene alkyl esters, and polyoxyethylene sorbitan alkyl esters; anionic emulsifiers such as salts of fatty acids such as myristic acid, palmitic acid, stearic acid, oleic acid, and linoleic acid, alkylbenzene sulfonates such as sodium dodecylbenzene sulfonate, polycondensates of naphthalene sulfonates and formalin, higher alcohol sulfates, and alkyl sulfosuccinates; and copolymerizable emulsifiers such as sulfoesters of α,β-unsaturated carboxylic acids, sulfate esters of α,β-unsaturated carboxylic acids, and sulfoalkylaryl ethers. The amount of emulsifier added is preferably 0.1 to 10 parts by weight, more preferably 0.5 to 5 parts by weight, based on 100 parts by weight of the monomers used in the polymerization.
[0046] The polymerization initiator is not particularly limited as long as it is a radical initiator, and examples thereof include inorganic peroxides such as potassium persulfate, sodium persulfate, ammonium persulfate, potassium perphosphate, and hydrogen peroxide; organic peroxides such as t-butyl peroxide, cumene hydroperoxide, p-menthane hydroperoxide, di-t-butyl peroxide, t-butylcumyl peroxide, acetyl peroxide, isobutyryl peroxide, octanoyl peroxide, dibenzoyl peroxide, 3,5,5-trimethylhexanoyl peroxide, t-butylperoxyisobutyrate, and diisopropylbenzene hydroperoxide; and azo compounds such as azobisisobutyronitrile, azobis-2,4-dimethylvaleronitrile, azobiscyclohexanecarbonitrile, and methyl azobisisobutyrate. These polymerization initiators can be used alone or in combination of two or more. As the polymerization initiator, inorganic or organic peroxides are preferred. When a peroxide is used as a polymerization initiator, it can be used as a redox polymerization initiator in combination with a reducing agent such as sodium bisulfite, ferrous sulfate, etc. The amount of the polymerization initiator added is preferably 0.01 to 2 parts by weight based on 100 parts by weight of the monomer used in the polymerization.
[0047] The molecular weight regulator is not particularly limited, but includes mercaptans such as t-dodecyl mercaptan, n-dodecyl mercaptan, octyl mercaptan, etc.; halogenated hydrocarbons such as carbon tetrachloride, methylene chloride, methylene bromide, etc.; α-methylstyrene dimer; sulfur-containing compounds such as tetraethyl thiuram disulfide, dipentamethylene thiuram disulfide, diisopropyl xanthogen disulfide, etc. These can be used alone or in combination of two or more kinds. Among them, mercaptans are preferred, and t-dodecyl mercaptan is more preferred. The amount of the molecular weight regulator to be added is preferably 0.1 to 5 parts by weight based on 100 parts by weight of the monomer used in polymerization.
[0048] Water is usually used as a medium for emulsion polymerization. The amount of water is preferably 80 to 500 parts by weight, more preferably 80 to 300 parts by weight, based on 100 parts by weight of the monomer used in the polymerization.
[0049] In the emulsion polymerization, if necessary, it is possible to use secondary polymerization materials such as stabilizers, dispersants, pH adjusters, oxygen scavengers, particle size adjusters, etc. When these are used, the types and amounts used are not particularly limited.
[0050] The copolymer obtained may be hydrogenated (hydrogenation reaction) as necessary. Hydrogenation may be carried out by a known method, such as an oil layer hydrogenation method in which the copolymer latex obtained by emulsion polymerization is coagulated and then hydrogenated in an oil layer, or an aqueous layer hydrogenation method in which the copolymer latex obtained is directly hydrogenated. In the present invention, however, the aqueous layer hydrogenation method is preferred from the viewpoint of simplifying the manufacturing process. According to the aqueous layer hydrogenation method, the nitrile rubber can be obtained in the form of a latex in which the nitrile rubber is dispersed in an aqueous medium, that is, as a latex of nitrile rubber (aqueous dispersion of nitrile rubber in which nitrile rubber particles are dispersed in water).
[0051] When hydrogenation is carried out by the aqueous phase hydrogenation method, the copolymer latex prepared by the above emulsion polymerization is preferably diluted by adding water as necessary, and hydrogenation reaction is carried out. The aqueous phase hydrogenation method includes an aqueous phase direct hydrogenation method in which hydrogen is supplied to a reaction system in the presence of a hydrogenation catalyst to carry out hydrogenation, and an aqueous phase indirect hydrogenation method in which hydrogenation is carried out by reduction in the presence of an oxidizing agent, a reducing agent, and an activating agent, and among these, the aqueous phase direct hydrogenation method is preferred.
[0052] The hydrogenation catalyst is not particularly limited as long as it is a compound that is not easily decomposed by water. Specific examples of the palladium catalyst include palladium salts of carboxylic acids such as formic acid, propionic acid, lauric acid, succinic acid, oleic acid, and phthalic acid; palladium chloride, dichloro(cyclooctadiene)palladium, dichloro(norbornadiene)palladium, and ammonium hexachloropalladate(IV); iodides such as palladium iodide; palladium nitrate; and palladium sulfate dihydrate. Among these, palladium salts of carboxylic acids, dichloro(norbornadiene)palladium and ammonium hexachloropalladate(IV) palladium chloride, and palladium nitrate are particularly preferred. As the hydrogenation catalyst, in addition to palladium catalysts containing palladium as a metal, ruthenium catalysts, rhodium catalysts, osmium catalysts, iridium catalysts, platinum catalysts, and the like can also be used. The amount of the metal (eg, palladium) in the hydrogenation catalyst used may be determined appropriately, but is preferably 5 to 20,000 ppm by weight, more preferably 10 to 15,000 ppm by weight, based on the copolymer obtained by polymerization.
[0053] In the aqueous phase direct hydrogenation method, the hydrogenation catalyst in the latex may be removed after the hydrogenation reaction is completed. For example, the hydrogenation catalyst may be adsorbed by adding an adsorbent such as activated carbon or ion exchange resin under stirring, or may be formed as a complex of the hydrogenation catalyst by using a complexing agent together with an oxidizing agent or a reducing agent, and then the latex may be centrifuged or filtered. The hydrogenation catalyst may be left in the latex without being removed.
[0054] <Method of manufacturing nitrile rubber> Next, a method for producing nitrile rubber by recovering nitrile rubber (solid nitrile rubber) from the nitrile rubber latex (aqueous dispersion of nitrile rubber) obtained as described above will be described. Note that, in the following, a case where an extruder 1 shown in Fig. 1 is used as a production device for recovering nitrile rubber from the nitrile rubber latex will be described as an example, but the present invention is not particularly limited to the method using the extruder 1 shown in Fig. 1.
[0055] 1, the extruder 1 has a drive unit 2 and a single barrel 3 composed of 18 divided barrel blocks 31 to 48. Inside the barrel 3, a coagulation zone 100, a drainage zone 102, a washing / dewatering zone 104, and a drying zone 106 are formed in this order from the upstream side to the downstream side of the barrel 3.
[0056] The coagulation zone 100 is a region where the nitrile rubber latex is brought into contact with a coagulant to coagulate the polymer and form a crumb-like nitrile rubber slurry liquid (crumb slurry). The drainage zone 102 is a region where the liquid (serum water) generated after the coagulation of the nitrile rubber is separated from the crumb slurry and discharged to form hydrous crumbs. The washing / dehydration zone 104 is a region where the hydrous crumbs are washed and the washing water is dehydrated and discharged from the washed crumbs. The drying zone 106 is a region where the dehydrated crumbs are dried.
[0057] In the extruder 1 shown in Fig. 1, the insides of the barrel blocks 31 to 36 correspond to a coagulation zone 100, the inside of the barrel block 37 corresponds to a drainage zone 102, the insides of the barrel blocks 38 to 41 correspond to a washing / dehydration zone 104, and the insides of the barrel blocks 42 to 48 correspond to a drying zone 106. The number of barrel blocks to be installed can be an optimum number depending on the composition of the nitrile rubber to be handled, and is not limited to the embodiment shown in Fig. 1.
[0058] The barrel block 32 constituting a part of the coagulation zone 100 is provided with a feed port 320 (not shown) for feeding nitrile rubber latex, a feed port 321 (not shown) for feeding a coagulant, and a feed port 322 (not shown) for feeding water vapor. The barrel block 37 constituting the drainage zone 102 is provided with a discharge slit 370 for discharging serum water separated from the water slurry of the coagulated nitrile rubber. The barrel block 38 constituting a part of the washing / dehydration zone 104 is provided with a washing water feed port 380 for receiving washing water, and the barrel block 39 is provided with a drainage slit 390 for discharging washing wastewater to the outside. The barrel blocks 43, 46, and 47 constituting a part of the drying zone 106 are provided with vent ports 430, 460, and 470 for deaeration, respectively.
[0059] Fig. 2 is a schematic diagram showing a screw disposed inside the extruder 1. A screw 5 as shown in Fig. 2 is disposed inside the barrel 3. A driving means such as a motor housed in a driving unit 2 (see Fig. 1) is connected to the base end of the screw 5 in order to drive the screw 5, thereby holding the screw 5 so that it can be rotated freely. The shape of the screw 5 is not particularly limited, but it can be configured, for example, by appropriately combining a screw block having various screw configurations and a kneading disc.
[0060] In the extruder 1, the screw 5 has different screw configurations in the regions corresponding to the above-mentioned zones 100, 102, 104, and 106 formed inside the barrel 3. Here, FIG. 3 is a partially cutaway schematic view of the screw in FIG. 2. As shown in FIG. 3, the screw 5 is composed of a screw block 50 and a kneading disc 52. Note that FIG. 3 is a view showing an example of a combination of the screw block 50 and the kneading disc 52, and the present invention is not particularly limited to the combination shown in FIG. 3.
[0061] 2, when the length of the screw 5 is L (mm) and the outer diameter of the screw 5 is Da (mm), L / Da is preferably 30 to 100, and more preferably 40 to 80. The outer diameter Da of the screw 5 is defined as the diameter of a thread portion 50A (see FIG. 3) of a screw block 50 constituting the screw, as viewed in the axial direction.
[0062] As shown in FIG. 4, the extruder 1 is a twin-screw extruder using two such screws 5 with their axes parallel to each other. Here, FIG. 4 is a cross-sectional view taken along line IV-IV in FIG. 1 and line IV-IV in FIG. 2, and the cross-sectional view shown in FIG. 4 is a cross-sectional view of the screw block 50 of the extruder 1, and is a cross-sectional view crossing the valley portion 50B. That is, as shown in FIG. 4, the two screws 5, 5 are of a twin-screw intermeshing type in which the crest portion 50A of the solidification screw block 50 of one screw 5 is intermeshed with the valley portion 50B of the solidification screw block 50 of the other screw 5, and the valley portion 50B of the solidification screw block 50 of one screw 5 is intermeshed with the crest portion 50A of the solidification screw block 50 of the other screw 5. By adopting the twin-screw intermeshing type, the mixing property in each of the zones 100, 102, 104, 106 can be improved. The rotation directions of the two screws 5 may be the same or different, but from the standpoint of self-cleaning performance, it is preferable that they rotate in the same direction.
[0063] 4, when the outer diameter of the screw block 50 is Da (mm) and the minor axis of the valley portion 50B of the screw block 50 is Di (mm), Da / Di is preferably in the range of 1.2 to 2.5, more preferably 1.4 to 2.0, and further preferably 1.5 to 1.8. By setting Da / Di in such a range, it is possible to improve the recovery rate and production rate (the amount of dried nitrile rubber obtained per unit time) without using large-scale equipment.
[0064] 4, the minor axis Di of valley portion 50B is the diameter of valley portion 50B at a depth Di' (mm) that is the deepest portion of valley portion 50B when viewed in the axial direction. That is, the minor axis Di of valley portion 50B can be calculated from the outer diameter Da and the deepest portion Di' of valley portion 50B by Di=Da-Di'×2.
[0065] The kneading disc 52 has a cross-sectional shape such as a pseudo-ellipse, an oval, or a truncated triangle, a certain thickness, and is stacked in a plurality of sheets while shifting the symmetrical axis of the cross-sectional shape by a predetermined angle, and the screw shaft is fixed so as to correspond to the rotation center axis of the cross-sectional shape. Here, FIG. 5 is a cross-sectional view along the VV line in FIG. 1 and the VV line in FIG. 2, and the cross-sectional view shown in FIG. 5 is a cross-sectional view of the kneading disc 52 part of the extruder 1. In FIG. 3 and FIG. 5, the kneading disc 52 has a pseudo-elliptical cross-sectional shape, and is shown in an embodiment in which five of them are stacked by shifting them by 45 degrees. However, the kneading disc 52 is not particularly limited to such an embodiment, and a plurality of kneading discs 52 can be combined by shifting them by a predetermined angle to form a forward kneading disc, a neutral kneading disc, or a reverse kneading disc. The forward kneading disc is a disc that has a feeding capability in the forward direction by shifting the phase of the multiple kneading discs 52 in the forward direction (for example, by shifting by 45° or by 60°), and the reverse kneading disc is a disc that has a feeding capability in the reverse direction by shifting the phase of the multiple kneading discs 52 in the reverse direction (for example, by shifting by 270°). The neutral kneading disc is a disc that has no feeding capability by forming the multiple kneading discs 52 in parallel to the axial direction with a shift of 90°.
[0066] 3 and 5, the kneading disk 52 has a pseudo-elliptical cross-sectional shape, but the pseudo-elliptical shape refers to a shape in which both ends of the major axis of an ellipse are cut by an arc with the center of rotation of the corresponding figure as the center, while the oval shape refers to a shape in which both ends of a parallel strip are cut by an arc with the center of rotation of the corresponding figure as the center, and the truncated triangle refers to a shape in which the parts including the vertices of an equilateral triangle are cut by an arc with the center of rotation of the corresponding figure as the center. In either shape, the end of each disk is provided on the inner wall surface 3a of the barrel 3 so as to maintain a predetermined clearance (gap) of about 0.1 to 5 mm. In the case of an oval shape or a truncated triangle, each side may be concave to form a drum shape or a triangular pincushion shape.
[0067] In addition, the die 4 is connected to the downstream side of the barrel block 48 described above, for extruding the nitrile rubber that has been solidified, dehydrated and dried in the barrel 3 into a predetermined shape to produce a product, for example, in the form of a sheet. In addition, the die 4 is usually provided with a wire mesh upstream of its discharge port to capture foreign matter and the like.
[0068] Next, a method for recovering nitrile rubber from nitrile rubber latex using such an extruder 1 will be described. First, nitrile rubber latex is supplied to the coagulation zone 100 through a pipe connected to the feed port 320, a coagulant through a pipe connected to the feed port 321, and steam through a pipe connected to the feed port 322. The coagulant is not particularly limited, but from the viewpoint of ensuring sufficient processability of the resulting nitrile rubber, a salt of a monovalent or divalent metal is preferably used. Specific examples of the coagulant include calcium chloride, magnesium chloride, sodium chloride, magnesium sulfate, barium chloride, and the like, and sodium chloride is particularly preferably used.
[0069] In the present invention, when the nitrile rubber latex is fed into the extruder 1, a hindered phenol-based antioxidant having a molecular weight of 300 to 3000 is added to the nitrile rubber latex before it is fed into the extruder 1, so that the nitrile rubber latex contains such a hindered phenol-based antioxidant, and the nitrile rubber latex is fed into the extruder 1 in a state in which the hindered phenol-based antioxidant is contained.
[0070] Specifically, a hindered phenol-based antioxidant having a molecular weight of 300 to 3000 is added to the latex of nitrile rubber before being fed into the extruder 1 at a ratio of 0.1 to 3 parts by weight per 100 parts by weight of nitrile rubber contained in the latex of nitrile rubber, and the latex is fed into the extruder 1 in the state where the hindered phenol-based antioxidant is added. According to the present invention, the specific amount of the hindered phenol-based antioxidant having a molecular weight of 300 to 3000 is added to the latex of nitrile rubber before being fed into the extruder 1, and the latex is fed into the extruder 1 together with a coagulant in the state where the hindered phenol-based antioxidant is added, thereby recovering the nitrile rubber from the latex of nitrile rubber, and the action of the specific amount of the hindered phenol-based antioxidant can effectively suppress the generation of dirt on the extruder 1 and the generation of dirt on the mold used during molding, and further, the processability of the obtained nitrile rubber (particularly, the processability when a crosslinking agent or the like is blended to form a rubber composition) can be made excellent.
[0071] The hindered phenol-based antioxidant may be a compound having a phenol structure, a bulky group (e.g., t-butyl group or octylthiomethyl group) at the two ortho positions of the OH group (phenolic hydroxyl group) constituting the phenol structure, and a molecular weight of 300 to 3000, or a compound having a bulky group (e.g., t-butyl group or octylthiomethyl group) at one of the two ortho positions of the OH group (phenolic hydroxyl group) constituting the phenol structure and a methyl group at the other ortho position, and a molecular weight of 300 to 3000. Examples of the hindered phenol-based antioxidant include, but are not limited to, 4,6-bis(octylthiomethyl)-o-cresol, 2,2'-methylenebis(4-methyl-6-t-butyl)- ethylphenol), 2,2'-methylenebis(4-ethyl-6-t-butylphenol), n-octadecyl-3-(3',5'-di-t-butyl-4'-hydroxyphenyl)propionate, 1,3,5-tris(3,5-di-t-butyl-4-hydroxybenzyl)-s-triazine-2,4,6-(1H,3H,5H)trione, pentaerythritol-tetrakis(3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate), N,N-hexamethylenebis(3,5-di-tert-butyl-4-hydroxy-hydrocinnamide), and tris(3,5-di-t-butyl-4-hydroxybenzyl)-isocyanurate. The molecular weight of the hindered phenol-based antioxidant is in the range of 300 to 3000, preferably 400 to 2000, more preferably 400 to 1200, even more preferably 400 to 1000, and even more preferably 400 to 600. When the molecular weight of the hindered phenol-based antioxidant is in the above-mentioned predetermined range, it is possible to effectively suppress the occurrence of staining of the extruder and to produce a nitrile rubber having excellent processability.
[0072] The amount of the hindered phenol-based antioxidant having a molecular weight of 300 to 3000 added to the latex of the nitrile rubber before being fed into the extruder 1 is 0.1 to 3 parts by weight, preferably 0.3 to 2.5 parts by weight, more preferably 0.5 to 2.0 parts by weight, even more preferably 0.7 to 2.0 parts by weight, and even more preferably 0.7 to 1.6 parts by weight, relative to 100 parts by weight of the nitrile rubber contained in the latex of the nitrile rubber. If the amount of the hindered phenol-based antioxidant having a molecular weight of 300 to 3000 used is too small, the obtained nitrile rubber will have poor processability. Alternatively, if the amount of the hindered phenol-based antioxidant having a molecular weight of 300 to 3000 used is too large, the mold used for molding will be stained when the obtained nitrile rubber is molded (or crosslinked at the same time as molding), resulting in poor productivity.
[0073] In addition, when an antioxidant other than a hindered phenol-based antioxidant having a molecular weight of 300 to 3000 is used, dirt will be generated in the extruder 1, more specifically, dirt will be generated in the vent ports 430, 460, and 470 of the extruder 1, resulting in poor productivity. In particular, if dirt is generated in the vent ports 430, 460, and 470 of the extruder 1, the generated dirt may fall into the extruder 1 and contaminate the nitrile rubber. Therefore, in order to prevent such contamination of the nitrile rubber, it becomes necessary to frequently remove the dirt generated in the vent ports 430, 460, and 470 of the extruder 1, which results in a decrease in productivity.
[0074] The method for adding the hindered phenol-based antiaging agent having a molecular weight of 300 to 3000 to the nitrile rubber latex before it is fed into the extruder 1 is not particularly limited, and the hindered phenol-based antiaging agent may be added directly to the nitrile rubber latex. However, from the viewpoint of more appropriately suppressing the occurrence of staining of the mold used during molding, it is preferable to emulsify the hindered phenol-based antiaging agent in water and add it in the form of an emulsion.
[0075] When the hindered phenol-based antioxidant having a molecular weight of 300 to 3000 is added in the form of an emulsion to the nitrile rubber latex before being fed into the extruder 1, it is preferable to use an emulsifier to make the emulsion. The emulsifier is not particularly limited and may be appropriately selected depending on the type of the hindered phenol-based antioxidant used, but for example, the emulsifiers used in the emulsion polymerization of the nitrile rubber described above may be used.
[0076] When a hindered phenol-based antioxidant having a molecular weight of 300 to 3000 is added in an emulsion state to the nitrile rubber latex before being fed into the extruder 1, the content of the hindered phenol-based antioxidant in the emulsion is not particularly limited, but from the viewpoint of being able to further enhance the effect of adding it in an emulsion state, it is preferably 1 to 70% by weight, more preferably 5 to 60% by weight, even more preferably 10 to 50% by weight, and even more preferably 15 to 25% by weight.
[0077] The amount of the coagulant supplied from the feed port 321 is preferably 0.5 to 200 parts by weight, more preferably 1 to 95 parts by weight, and even more preferably 45 to 75 parts by weight, relative to 100 parts by weight of the nitrile rubber contained in the latex of the nitrile rubber. By setting the amount of the coagulant supplied within the above range, the coagulation of the nitrile rubber can be sufficiently advanced, the uncoagulated portion can be reduced, and the yield can be improved. The coagulant may be dissolved in water or the like and supplied from the feed port 321 as a coagulation liquid. In this case, the concentration of the coagulant in the coagulation liquid is not particularly limited, but is preferably about 1 to 35% by weight, more preferably 15 to 25% by weight, relative to the entire coagulation liquid.
[0078] The nitrile rubber latex, coagulant and steam supplied to the coagulation zone 100 are brought into contact with each other by the rotation of the screw 5, and the nitrile rubber is coagulated into crumbs having a diameter of about 5 to 30 mm and suspended in water, forming a slurry liquid (crumb slurry) with a crumb concentration of about 5 to 30% by weight. The temperature inside the coagulation zone 100 is preferably 10 to 100°C, more preferably 45 to 90°C. By setting the temperature of the coagulation zone 100 in this range, the coagulation of the nitrile rubber can be improved while the coagulation of the nitrile rubber can be sufficiently advanced, the uncoagulated portion can be reduced, and the yield can be improved.
[0079] The crumb slurry obtained in the coagulation zone 100 is sent to the drainage zone 102 by the rotation of the screw 5. In the drainage zone 102, the high concentration of coagulant contained in the crumb slurry is discharged as serum water from the slit 370 provided in the barrel block 37, and hydrated crumbs containing about 40 to 70% by weight of moisture are obtained.
[0080] The crumbs in a water-containing state obtained in the drainage zone 102 are sent to the washing / dewatering zone 104 by the rotation of the screw 5. In the washing / dewatering zone 104, washing water is introduced into the inside from a washing water feed port 380 provided in the barrel block 38, and the washing water and the crumbs are mixed, so that the crumbs are washed and then dewatered. The washed wastewater is discharged from a slit 390 provided in the barrel block 39.
[0081] The screw configuration of the screw 5 in the portion corresponding to the washing water feed port 380 provided in the barrel block 38 constituting the washing / dehydration zone 104 (i.e., the screw configuration of the screw 5 at the outlet of the washing water feed port 380) is configured from a plurality of kneading discs 52. By configuring the screw configuration of the screw 5 in the portion corresponding to the washing water feed port 380 to be configured from a plurality of kneading discs 52, the washing water supplied from the washing water feed port 380 can be supplied at an increased water pressure, thereby improving the washing efficiency. This makes it possible to appropriately reduce the sodium content and the total content of calcium, magnesium and aluminum in the recovered nitrile rubber, which are caused by the coagulant and the like, and to improve the water resistance of the obtained nitrile rubber.
[0082] In particular, by configuring the portion of the screw 5 corresponding to the wash water feed port 380 with a plurality of kneading discs 52, the spatial volume of the portion is reduced due to the presence of the plurality of kneading discs 52 and the presence of crumbs kneaded by the plurality of kneading discs 52, and the diffusion of the wash water supplied from the wash water feed port 380 in the barrel block 38 is suppressed (or the flow path becomes difficult to ensure), thereby making it possible to increase the water pressure of the supplied wash water. Note that, when the portion corresponding to the wash water feed port 380 is configured with a plurality of kneading discs 52, the disc configuration is not particularly limited, but it is preferable to use forward kneading discs, neutral kneading discs, or reverse kneading discs, and these may be combined.
[0083] In the present invention, the portion of the screw 5 corresponding to the wash water feed port 380 may be composed of a plurality of kneading discs 52. From the viewpoint of more appropriately increasing the water pressure of the supplied wash water, it is preferable to configure the screw configuration of the screw 5 in the barrel block 38 in which the wash water feed port 380 is formed such that the proportion (proportion in the length direction) of the kneading discs 52 is 30 to 100%, and it is more preferable to configure the screw configuration such that the proportion of the kneading discs 52 is 60 to 100%. By configuring in this way, the efficiency of washing crumbs in the washing / dewatering zone 104 can be further improved.
[0084] The proportion (proportion in the length direction) of the kneading discs 52 in the screw 5 in the entire washing / dehydration zone 104 is not particularly limited, but from the viewpoint of increasing not only the washing efficiency but also the dehydration efficiency, it is preferably 5 to 85%, more preferably 10 to 80%.
[0085] The supply rate of the washing water supplied from the washing water feed port 380 is not particularly limited, but is preferably 30 to 600 L / hr, more preferably 70 to 500 L / hr. The amount of the washing water supplied from the washing water feed port 380 is preferably 25 to 1000 parts by weight, more preferably 50 to 900 parts by weight, relative to 100 parts by weight of the nitrile rubber. By setting the supply rate of the washing water and the amount of the washing water within the above ranges, respectively, the washing effect in the washing / dehydration zone 104 can be further improved, and thus the content of sodium and the total content of calcium, magnesium and aluminum, which are caused by the coagulant, etc., in the recovered nitrile rubber can be more effectively reduced. The temperature of the washing water is not particularly limited, but is preferably 10 to 90°C, more preferably 40 to 80°C.
[0086] In the washing / dehydration zone 104, in the region before the wash water feed port 380, the barrel block temperature is preferably 40 to 100° C., and more preferably 50 to 95° C. In the region after the wash water feed port 380, the barrel block temperature is preferably 80 to 200° C., and more preferably 90 to 180° C. Then, in the washing / dehydration zone 104, washed crumbs containing about 2 to 20% by weight of moisture are obtained.
[0087] Next, the crumbs obtained in the washing / dehydration zone 104 are sent to the drying zone 106 by the rotation of the screw 5. The crumbs sent to the drying zone 106 are plasticized and kneaded by the rotation of the screw 5 to become a melt, and are transported downstream while generating heat and increasing in temperature. When the melt reaches the vent ports 430, 460, and 470 provided in the barrel blocks 43, 46, and 47, the pressure is released, and the moisture contained in the melt is separated and vaporized. The separated and vaporized moisture (steam) is discharged to the outside through a vent pipe (not shown). The temperature inside the drying zone 106 is preferably 90 to 200°C, and more preferably 100 to 180°C. The internal pressure (pressure at the die section) is about 1000 to 13000 kPa (G: gauge pressure). The drying zone 106 may be decompressed.
[0088] The crumbs from which moisture has been separated after passing through the drying zone 106 are sent to the outlet side by the screw 5 and introduced into the die 4 in a state containing substantially little moisture (moisture content of 1.0% by weight or less), where they are discharged, for example, in the form of a sheet, and then introduced into a sheet cutter (not shown) and cut to an appropriate length. In this manner, nitrile rubber can be recovered from the nitrile rubber latex.
[0089] In the present invention, when the amount of nitrile rubber fed to the feed port 320 of the extruder 1 per unit time (the amount of nitrile rubber recovered by the extruder 1 per unit time) is Q [kg / hr] and the rotation speed of the screw 5 is N [rpm], it is preferable to set the conditions such that Q / N [kg / (hr·rpm)] is 0.22 kg / (hr·rpm) or less, more preferably 0.21 kg / (hr·rpm) or less, and even more preferably 0.16 to 0.20 kg / (hr·rpm). The rotation speed N of the screw 6 is the rotation speed [rpm] when the screw 5 rotates in the barrel 3 of the extruder 1 per minute. By setting Q / N within the above range, even if the production rate (processing amount) is relatively high, the amount of volatile matter such as water contained in the recovered nitrile rubber can be effectively reduced, and thereby, problems such as inhibition of crosslinking due to remaining volatile matter such as water can be effectively suppressed, and as a result, when it is made into a rubber crosslinked product, it can be made to have excellent mechanical strength. The amount of volatile matter such as water contained in the recovered nitrile rubber is preferably 0.7% by weight or less, and more preferably 0.5% by weight or less.
[0090] The nitrile rubber thus recovered preferably has a maximum chemiluminescence intensity measured in accordance with JIS K7351:2018 of 2,000 to 25,000 counts / second, more preferably 3,000 to 20,000 counts / second, even more preferably 5,000 to 20,000 counts / second, and particularly preferably 6,000 to 15,000 counts / second. By setting the maximum chemiluminescence intensity within the above range, the processability of the recovered nitrile rubber (particularly, the processability when a crosslinking agent or the like is blended to form a rubber composition) can be more appropriately improved. The maximum value of the chemiluminescence intensity can be measured, for example, by cutting a sample of nitrile rubber into a square of 1 cm square and a thickness of 2 mm with a razor, using this as a measurement sample, and measuring it with a chemiluminescence analyzer under conditions of a measurement temperature of 170 ° C., a N2 gas flow rate of 150 ml / min, and a measurement time of 600 seconds in accordance with JIS K 7351: 2018 (High sensitivity measurement method for weak luminescence of peroxide contained in plastics). Examples of a method for setting the maximum value of the chemiluminescence intensity within the above range include a method of adjusting the type and amount of a hindered phenol-based antiaging agent having a molecular weight of 300 to 3000 that is added in advance to the latex of nitrile rubber before being put into the extruder 1, a method of adjusting the configuration of the screw 5 of the extruder 1, the rotation speed of the screw 5 of the extruder 1, and a method of adjusting the temperature of the drying zone 106 of the extruder 1.
[0091] <Rubber composition> The nitrile rubber produced as described above can be used as a rubber composition by blending a crosslinking agent therein. The crosslinking agent is not particularly limited, but may be a sulfur crosslinking agent, an organic peroxide crosslinking agent, or a polyamine crosslinking agent. Among these, when the nitrile rubber produced as described above is a carboxyl group-containing nitrile rubber, a polyamine crosslinking agent is preferred.
[0092] The polyamine-based crosslinking agent is not particularly limited as long as it is a compound having two or more amino groups, or a compound that becomes a compound having two or more amino groups upon crosslinking. However, a compound in which multiple hydrogen atoms of an aliphatic hydrocarbon or aromatic hydrocarbon are substituted with amino groups or a hydrazide structure (a structure represented by -CONHNH2, where CO represents a carbonyl group), or a compound that becomes such a compound upon crosslinking, is preferred.
[0093] Specific examples of polyamine-based crosslinking agents include aliphatic polyamines such as hexamethylenediamine, hexamethylenediamine carbamate, N,N-dicinnamylidene-1,6-hexanediamine, tetramethylenepentamine, and hexamethylenediamine cinnamaldehyde adduct; 4,4-methylenedianiline, m-phenylenediamine, 4,4-diaminodiphenyl ether, 3,4-diaminodiphenyl ether, 4,4-(m-phenylenediisopropylidene)dianiline, 4,4-(p-phenylenediisopropylidene)dianiline, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, 4,4-diaminobenzanilide, 4,4-bis(4-aminophenoxy)biphenyl, m-xylylenediamine, p-xylylenediamine, and 1,3,5-benzenetriamine. Aromatic polyamines; isophthalic dihydrazide, terephthalic dihydrazide, phthalic dihydrazide, 2,6-naphthalenedicarboxylic dihydrazide, naphthalene dihydrazide, oxalic dihydrazide, malonic dihydrazide, succinic dihydrazide, glutamic dihydrazide, adipic dihydrazide, pimelic dihydrazide, suberic dihydrazide, azelaic dihydrazide dihydrazide, sebacic acid dihydrazide, brassylic acid dihydrazide, dodecanedioic acid dihydrazide, acetonedicarboxylic acid dihydrazide, fumaric acid dihydrazide, maleic acid dihydrazide, itaconic acid dihydrazide, trimellitic acid dihydrazide, 1,3,5-benzenetricarboxylic acid dihydrazide, aconitic acid dihydrazide, pyromellitic acid dihydrazide, and other polyhydric hydrazides. Among these, aliphatic polyhydric amines and aromatic polyhydric amines are preferred, hexamethylenediamine carbamate and 2,2-bis[4-(4-aminophenoxy)phenyl]propane are more preferred, and hexamethylenediamine carbamate is particularly preferred, in that the effects of the present invention can be made even more remarkable.
[0094] The content of the crosslinking agent in the rubber composition of the present invention is not particularly limited, but is preferably 0.1 to 20 parts by weight, more preferably 0.2 to 15 parts by weight, and further preferably 0.5 to 10 parts by weight, based on 100 parts by weight of the nitrile rubber.
[0095] In addition to the crosslinking agent, the rubber composition of the present invention may contain compounding agents that are commonly used in the rubber field, such as fillers, metal oxides such as zinc oxide and magnesium oxide, α,β-ethylenically unsaturated carboxylic acid metal salts such as zinc methacrylate and zinc acrylate, crosslinking accelerators, co-crosslinking agents, crosslinking assistants, crosslinking retarders, antioxidants, antioxidants, light stabilizers, scorch inhibitors such as primary amines, activators such as diethylene glycol, silane coupling agents, plasticizers, processing aids, slip agents, adhesives, lubricants, flame retardants, antifungal agents, acid acceptors, antistatic agents, pigments, foaming agents, etc. The amounts of these compounding agents are not particularly limited as long as they do not impair the purpose and effects of the present invention, and they may be compounded in amounts according to the purpose of compounding.
[0096] Furthermore, the rubber composition of the present invention may contain rubber other than nitrile rubber.
[0097] <Rubber cross-linked products> Moreover, the above-mentioned rubber composition can be crosslinked to form a crosslinked rubber product. The cross-linked rubber product of the present invention can be produced by using the rubber composition of the present invention, molding the rubber composition into a desired shape using a molding machine such as an extruder, an injection molding machine, a compressor, or a roll, and heating the composition to cause a cross-linking reaction and fix the shape as a cross-linked product. In this case, the cross-linking may be carried out after molding in advance or simultaneously with molding. The molding temperature is usually 10 to 200°C, preferably 25 to 120°C. The cross-linking temperature is usually 100 to 200°C, preferably 130 to 190°C, and the cross-linking time is usually 1 minute to 24 hours, preferably 2 minutes to 1 hour.
[0098] Depending on the shape, size, etc. of the crosslinked product, even if the surface is crosslinked, the inside may not be sufficiently crosslinked, so secondary crosslinking may be performed by further heating. As the heating method, a general method used for crosslinking rubber, such as press heating, steam heating, oven heating, or hot air heating, may be appropriately selected.
[0099] The cross-linked rubber of the present invention is obtained by using a rubber composition containing the above-mentioned nitrile rubber of the present invention. The cross-linked rubber of the present invention can be used in a wide variety of applications, including, for example, O-rings, packings, diaphragms, oil seals, shaft seals, bearing seals, wellhead seals, shock absorber seals, coolant seals and oil coolant seals which are seals for cooling liquids such as long-life coolant (LLC), seals for pneumatic equipment, seals for sealing fluorocarbons, fluorohydrocarbons or carbon dioxide used in the cooling devices of air conditioners and compressors for refrigeration units of air conditioners, seals for sealing supercritical carbon dioxide or subcritical carbon dioxide used as a cleaning medium in precision cleaning, seals for rolling devices (rolling bearings, hub units for automobiles, water pumps for automobiles, linear guide devices and ball screws, etc.), valves and valve seats, BOP (Blow Out) seals, and the like. various sealing materials such as sealants (seal protectors) and bladders; intake manifold gaskets attached to the joint between the intake manifold and cylinder head, cylinder head gaskets attached to the joint between the cylinder block and cylinder head, rocker cover gaskets attached to the joint between the rocker cover and cylinder head, oil pan gaskets attached to the joint between the oil pan and cylinder block or transmission case, gaskets for fuel cell separators attached between a pair of housings that sandwich a unit cell having a positive electrode, an electrolyte plate, and a negative electrode. gaskets for hard disk drives and other top cover gaskets; rolls for printing, steelmaking, papermaking, industrial, and office equipment; flat belts (film core flat belts, cord flat belts, laminated flat belts, single flat belts, etc.), V-belts (wrapped V-belts, raw edge V-belts, etc.), V-ribbed belts (single V-ribbed belts, double V-ribbed belts, wrapped V-ribbed belts, rubber backed V-ribbed belts, upper cog V-ribbed belts, etc.), CVT belts, timing belts, toothed belts, conveyor belts, and other belts;It can be used for a wide range of applications, including fuel hoses, turbo air hoses, oil hoses, radiator hoses, heater hoses, water hoses, vacuum brake hoses, control hoses, air conditioning hoses, brake hoses, power steering hoses, air hoses, marine hoses, risers, and flow lines; CVJ boots, propeller shaft boots, constant velocity joint boots, rack and pinion boots, and other boots; cushioning materials, dynamic dampers, rubber couplings, air springs, vibration-proof materials, clutch facing materials, and other damping rubber parts; dust covers, automotive interior materials, friction materials, tires, coated cables, shoe soles, electromagnetic wave shields, adhesives such as adhesives for flexible printed circuit boards, fuel cell separators, and other electronics fields. EXAMPLES
[0100] The present invention will be described in more detail below with reference to examples and comparative examples. In each example, "parts" is by weight unless otherwise specified. Various physical properties were evaluated according to the following methods.
[0101] [Content of each monomer unit constituting hydrogenated nitrile rubber] The content ratio of mono-n-butyl maleate units was calculated by adding 100 mL of 2-butanone to 0.2 g of 2 mm square hydrogenated nitrile rubber, stirring for 16 hours, adding 20 mL of ethanol and 10 mL of water, and titrating with 0.02 N aqueous ethanol solution of potassium hydroxide at room temperature using thymolphthalein as an indicator while stirring to determine the number of moles of carboxyl groups per 100 g of hydrogenated nitrile rubber, and converting the determined number of moles into the amount of mono-n-butyl maleate units. The content ratio of 1,3-butadiene units and saturated butadiene units was calculated by measuring the iodine value (according to K6235:2006) before and after the hydrogenation reaction using hydrogenated nitrile rubber. The content of acrylonitrile units was calculated by measuring the nitrogen content in the hydrogenated nitrile rubber by the Kjeldahl method in accordance with JIS K6451-2:2016. The content of n-butyl acrylate units was calculated as the remaining component relative to each of the above monomer units.
[0102] [Mooney Viscosity of Hydrogenated Nitrile Rubber] The Mooney viscosity of the hydrogenated nitrile rubber (polymer Mooney, ML1+4, 100°C) was measured at 100°C in accordance with JIS K6300-1:2013.
[0103] [Mooney Viscosity of Rubber Composition] The Mooney viscosity of the rubber composition (compound Mooney, ML1+4, 100°C) was measured at 100°C in accordance with JIS K6300-1:2013.
[0104] [Maximum chemiluminescence intensity of hydrogenated nitrile rubber] The collected hydrogenated nitrile rubber was cut into 1 cm squares and 2 mm thick samples with a razor to prepare measurement samples, and the chemiluminescence intensity of the measurement sample was measured using a chemiluminescence analyzer (Tohoku Electronics Industries, product name "CLA-FS4") under conditions of a measurement temperature of 170°C, a N2 gas flow rate of 150 ml / min, and a measurement time of 600 seconds in accordance with JIS K 7351:2018 (High sensitivity measurement method for weak luminescence of peroxide contained in plastics). The maximum chemiluminescence intensity within the measurement time was then determined from the measurement results.
[0105] [Volatile content of hydrogenated nitrile rubber] The volatile content of the hydrogenated nitrile rubber was measured in accordance with JIS K 6238-1:2009 (oven A method), and the hydrogenated nitrile rubber was dried at 105°C ± 5°C for 1 hour, and then allowed to cool in a desiccator. The volatile content (wt%) was calculated from the weight difference before and after drying according to [(rubber weight before drying - rubber weight after drying) / (rubber weight before drying)] × 100.
[0106] [Extruder Dirt] After the coagulation, washing, dehydration and drying of the hydrogenated nitrile rubber latex (L1) was performed continuously for 6 hours using the extruder 1, the vent port 430 of the extruder 1 was visually inspected for dirt (the state of contamination of the vent port due to attached rubber, compounding agents, etc.) and evaluated according to the following criteria. ◎: No stains ○: Slightly dirty △: Clearly dirty ×: Very dirty
[0107] [Mold stain resistance] The mold staining property was evaluated as follows: First, a test piece of about 150 mm in length, about 80 mm in width, and about 2 mm in thickness was prepared from the uncrosslinked rubber composition, and this was sandwiched in a sheet mold of 150 mm x 80 mm x 2 mm. Then, the test piece was subjected to a pressure of 100 kg / cm at 180°C. 3 The press crosslinking was carried out five times for 10 minutes at a pressure of 1000 MPa, and the dirt on the mold surface during press crosslinking (the state of mold contamination due to adhering rubber and compounding agents, etc.) was visually observed and evaluated according to the following criteria. ◎: No stains ○: Slightly dirty △: Clearly dirty ×: Very dirty
[0108] [Production Example 1, Production of Hydrogenated Nitrile Rubber Latex (L1)] In a metal bottle, 180 parts of ion-exchanged water, 25 parts of a 10% concentration sodium dodecylbenzenesulfonate aqueous solution, 5 parts of a 10% concentration sodium salt of naphthalenesulfonic acid formalin condensate, 20.4 parts of acrylonitrile, 5 parts of mono n-butyl maleate, 35.2 parts of n-butyl acrylate, and 0.75 parts of t-dodecyl mercaptan (molecular weight modifier) were charged in this order, and the gas inside was replaced with nitrogen three times, and then 39.4 parts of 1,3-butadiene was charged. The metal bottle was kept at 10°C, and 0.1 parts of cumene hydroperoxide (polymerization initiator) and an appropriate amount of a reducing agent, a chelating agent, and a builder were charged, and the polymerization reaction was continued while stirring. When the polymerization conversion rate reached 80%, 4 parts of a 2.5% concentration 2,2,6,6-tetramethylpiperidine-1-oxyl aqueous solution (polymerization terminator) were added to stop the polymerization reaction. Next, the residual monomer was removed using water at a temperature of 60° C. to obtain a nitrile rubber latex (X1) (solid content concentration: 28% by weight).
[0109] Separately from the above, an aqueous palladium solution was obtained by adding an aqueous solution containing sodium chloride in an amount twice the molar equivalent of the Pd metal in palladium chloride to palladium chloride (weight ratio of Pd metal in palladium chloride / nitrile rubber in latex: 2800 ppm by weight). Then, polyvinylpyrrolidone with a weight average molecular weight of 5,000 was added to 300 parts of the obtained aqueous palladium solution in an amount that was 5 times the weight ratio of the Pd metal in palladium chloride, and an aqueous potassium hydroxide solution was further added to prepare an aqueous catalyst solution with a pH of 12.0.
[0110] Next, the nitrile rubber latex (X1) obtained above and the catalyst aqueous solution prepared above were added to an autoclave so that the palladium content relative to the dry weight of the rubber contained in the nitrile rubber latex (X1) obtained above was 2800 ppm by weight, and a hydrogenation reaction was carried out for 6 hours at a hydrogen pressure of 3 MPa and a temperature of 50°C to obtain a hydrogenated nitrile rubber latex (L1) (solid content concentration: 13.5% by weight). The composition of the hydrogenated nitrile rubber contained in the obtained hydrogenated nitrile rubber latex (L1) was 20.5% by weight of acrylonitrile units, 45.5% by weight of 1,3-butadiene units (including saturated portions), 5.0% by weight of mono-n-butyl maleate units, and 29% by weight of n-butyl acrylate units, and the iodine value was 7.
[0111] [Example 1] To the hydrogenated nitrile rubber latex (L1) obtained in Production Example 1, 0.8 parts of 4,6-bis(octylthiomethyl)-o-cresol (manufactured by BASF Japan, trade name "Irganox 1520L", molecular weight: 424.8) as a hindered phenol-based antiaging agent was added in the form of an emulsion dispersed in 1.5 parts of a 20% by weight aqueous solution of sodium alkylbenzene sulfonate, relative to 100 parts by weight of the solid content in the latex, to prepare a latex (solid content concentration: 13.5% by weight) to which a hindered phenol-based antiaging agent was added.
[0112] Next, the latex to which the hindered phenol-based antioxidant was added prepared above was adjusted to pH=3.6 (solid content concentration: 13.5% by weight) using an aqueous sulfuric acid solution, and then, using an aqueous sodium chloride solution (concentration: 25% by weight) and water vapor as a coagulating liquid, the latex (L1) of the hydrogenated nitrile rubber was coagulated, washed, dehydrated and dried by the extruder 1 shown in FIG. 1 to recover solid hydrogenated nitrile rubber.
[0113] The extruder 1 used was a twin-screw intermeshing type extruder that rotates in the same direction, with two screws (cylinder diameter = 47 mm, L / Da = 63) 5, 5 arranged in parallel inside the barrel 3, and these screws 5, 5 rotated in the same direction with the crests of one screw meshing with the valleys of the other screw and the valleys of one screw meshing with the crests of the other screw.
[0114] In addition, the axial screw length L1 of the region corresponding to the coagulation zone 100 was 931 mm, the axial screw length L2 of the region corresponding to the drainage zone 102 was 161 mm, the axial screw length L3 of the region corresponding to the washing / dewatering zone 104 was 678 mm, and the axial screw length L4 of the region corresponding to the drying zone 106 was 1058 mm.
[0115] In Example 1, the two screws 5, 5 had the screw configuration shown below, and the set temperatures of each barrel block were as follows: barrel block 31-39: 90°C, barrel block 40-43: 130-140°C, and barrel block 44-48: 120-130°C. Barrel Block 38 screw configuration "BAAAAC" Barrel Block 40 screw configuration "DDDDAA" In addition, "A" means a forward kneading disc, "B" means a neutral kneading disc, "C" means a reverse kneading disc, and "D" means a full-flight screw. In other words, the screw configuration in the portion corresponding to the wash water feed port 380 is configured with a plurality of kneading discs, and the ratio of the screw occupied by the kneading discs in the barrel block 38 (the ratio occupied in the length direction) is 100%.
[0116] Then, from the feed port 320 provided in the barrel block 32 of the extruder 1 having such a configuration, the hydrogenated nitrile rubber latex (L1) adjusted to pH=3.6 was continuously supplied at a rate of 370 kg / hr (50 kg / hr in terms of hydrogenated nitrile rubber). At the same time, from the feed port 321 provided in the barrel block 32, a sodium chloride aqueous solution (coagulant concentration: 25% by weight) was continuously supplied at a rate of 120 kg / hr, and from the feed port 322 provided in the barrel block 32, steam was continuously supplied at a rate of 80 kg / hr under a pressure of 0.35 MPa. That is, the concentration of the coagulant relative to the total amount of serum water when passing through the feed port 321 [amount of sodium chloride / (amount of serum water consisting of all the supplies)] was set to 5.8% by weight, and the amount was set to 60 parts of sodium chloride per 100 parts of hydrogenated nitrile rubber. At the same time, washing water at a temperature of 60°C was continuously supplied from the washing water feed port 380 provided in the barrel block 38 under the condition of 350 L / hr, and the extruder 1 was operated at a screw rotation speed of 280 rpm, whereby the solid hydrogenated nitrile rubber was continuously recovered at a rate of 48 kg / hr by continuously carrying out coagulation, washing, dehydration and drying of the hydrogenated nitrile rubber latex (L1). The water pressure of the washing water supplied from the washing water feed port 380 provided in the barrel block 38 at this time was measured with a water pressure gauge provided near the washing water feed port 380, and was 4.0 MPa. In Example 1, Q (supply rate of hydrogenated nitrile rubber) / N (screw rotation speed) was 0.18.
[0117] Then, according to the above-mentioned method, the occurrence of dirt at the vent port 430 during the recovery operation of the hydrogenated nitrile rubber by the extruder 1 was evaluated, and the Mooney viscosity (polymer Mooney), maximum chemiluminescence intensity, and volatile matter content of the recovered hydrogenated nitrile rubber were measured. The results are shown in Table 1.
[0118] Next, using a Banbury mixer, 100 parts of MT carbon (Cancarb, trade name "Thermax MT", thermal black), 20 parts of tri-2-ethylhexyl trimellitate (ADEKA, trade name "Adeka Cizer C-8", plasticizer), 1.5 parts of 4,4'-di-(α,α-dimethylbenzyl)diphenylamine (Ouchi Shinko Chemical Industry, trade name "Nocrac CD", antioxidant), 1 part of stearic acid, and 1 part of polyoxyethylene alkyl ether phosphate (Toho Chemical Industry, trade name "Phosphanol RL210", processing aid) were added to 100 parts of the hydrogenated nitrile rubber recovered above, and mixed at 50°C for 5 minutes. The resulting mixture was then transferred to a roll at 50°C, and 4 parts of a mixture of dicyclohexylamine salt of ethylene glycol and long-chain alcohol (manufactured by Ouchi Shinko Chemical Industry Co., Ltd., product name "Knockmaster EGS", consisting of 80% by weight of dicyclohexylamine salt of ethylene glycol and 20% by weight of long-chain alcohol (1-tetradecanol, 1-hexadecanol, 1-octadecanol), a basic crosslinking accelerator) and 2.2 parts of hexamethylenediamine carbamate (manufactured by DuPont Dow Elastomers, product name "Diak#1", a polyamine crosslinking agent belonging to aliphatic polyamines) were blended and kneaded to obtain a rubber composition. The obtained rubber composition was used to measure the Mooney viscosity (compound Mooney) and evaluate the mold fouling properties according to the above-mentioned methods. The results are shown in Table 1.
[0119] [Example 2] A latex (solid content concentration: 13.5% by weight) containing a hindered phenol-based antioxidant was obtained in the same manner as in Example 1, except that 4,6-bis(octylthiomethyl)-o-cresol was added as a hindered phenol-based antioxidant to the latex (L1) of hydrogenated nitrile rubber obtained in Production Example 1, instead of in the form of an emulsion. The obtained latex containing a hindered phenol-based antioxidant was adjusted to pH=3.6 using an aqueous sulfuric acid solution (solid content concentration: 13.5% by weight), and then the solid hydrogenated nitrile rubber was continuously recovered at a rate of 48 kg / hr by coagulating, washing, dehydrating and drying the latex (L1) of hydrogenated nitrile rubber in the same manner as in Example 1. The recovered hydrogenated nitrile rubber was used to perform evaluation in the same manner as in Example 1, and a rubber composition was prepared and evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0120] [Example 3] A latex (solid content concentration: 13.5% by weight) containing a hindered phenol-based antioxidant was obtained in the same manner as in Example 1, except that an emulsion of 4,6-bis(octylthiomethyl)-o-cresol prepared in the same manner as in Example 1 was added to the hydrogenated nitrile rubber latex (L1) obtained in Production Example 1 so that the amount of 4,6-bis(octylthiomethyl)-o-cresol added as a hindered phenol-based antioxidant was 1.5 parts relative to 100 parts of solid content in the latex. Then, using the obtained latex containing a hindered phenol-based antioxidant, a sulfuric acid aqueous solution was used to adjust the pH to 3.6 (solid content concentration: 13.5% by weight), and the hydrogenated nitrile rubber latex (L1) was coagulated, washed, dehydrated, and dried in the same manner as in Example 1, whereby solid hydrogenated nitrile rubber was continuously recovered at a rate of 48 kg / hr. In addition, the recovered hydrogenated nitrile rubber was used to perform evaluation in the same manner as in Example 1, and a rubber composition was prepared and similarly evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0121] [Example 4] A latex (solid content concentration: 13.5% by weight) containing a hindered phenol-based antioxidant was obtained in the same manner as in Example 1, except that an emulsion of 4,6-bis(octylthiomethyl)-o-cresol prepared in the same manner as in Example 1 was added to the hydrogenated nitrile rubber latex (L1) obtained in Production Example 1 so that the amount of 4,6-bis(octylthiomethyl)-o-cresol added as a hindered phenol-based antioxidant was 2.2 parts relative to 100 parts of solid content in the latex. Then, using the obtained latex containing a hindered phenol-based antioxidant, a sulfuric acid aqueous solution was used to adjust the pH to 3.6 (solid content concentration: 13.5% by weight), and the hydrogenated nitrile rubber latex (L1) was coagulated, washed, dehydrated, and dried in the same manner as in Example 1, whereby solid hydrogenated nitrile rubber was continuously recovered at a rate of 48 kg / hr. In addition, the recovered hydrogenated nitrile rubber was used to perform evaluation in the same manner as in Example 1, and a rubber composition was prepared and evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0122] [Example 5] A latex (solid content concentration: 13.5% by weight) containing a hindered phenol-based antioxidant was obtained in the same manner as in Example 1, except that an emulsion of 4,6-bis(octylthiomethyl)-o-cresol prepared in the same manner as in Example 1 was added to the hydrogenated nitrile rubber latex (L1) obtained in Production Example 1 so that the amount of 4,6-bis(octylthiomethyl)-o-cresol added as a hindered phenol-based antioxidant was 0.3 parts relative to 100 parts of solid content in the latex. Then, using the obtained latex containing a hindered phenol-based antioxidant, a sulfuric acid aqueous solution was used to adjust the pH to 3.6 (solid content concentration: 13.5% by weight), and the hydrogenated nitrile rubber latex (L1) was coagulated, washed, dehydrated, and dried in the same manner as in Example 1, whereby solid hydrogenated nitrile rubber was continuously recovered at a rate of 48 kg / hr. In addition, the recovered hydrogenated nitrile rubber was used to perform evaluation in the same manner as in Example 1, and a rubber composition was prepared and evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0123] [Example 6] To the hydrogenated nitrile rubber latex (L1) obtained in Production Example 1, 0.8 parts of pentaerythritol-tetrakis(3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate) (manufactured by BASF Japan, trade name "Irganox 1010", molecular weight: 1177.6) as a hindered phenol-based antiaging agent was added in the form of an emulsion dispersed in 1.5 parts of a 20% by weight aqueous solution of sodium alkylbenzenesulfonate, relative to 100 parts by weight of the solid content in the latex, to prepare a latex (solid content concentration: 13.5% by weight) to which a hindered phenol-based antiaging agent was added. Then, the obtained latex to which the hindered phenol-based antioxidant was added was used, and the pH was adjusted to 3.6 using an aqueous sulfuric acid solution (solid content concentration: 13.5% by weight), and the solid hydrogenated nitrile rubber was continuously recovered at a rate of 48 kg / hr by carrying out coagulation, washing, dehydration and drying of the hydrogenated nitrile rubber latex (L1) in the same manner as in Example 1. The recovered hydrogenated nitrile rubber was used to perform evaluation in the same manner as in Example 1, and a rubber composition was prepared and evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0124] [Example 7] Using the latex containing the hindered phenol-based antioxidant obtained in the same manner as in Example 1, and changing the screw rotation speed of the extruder 1 to 330 rpm (i.e., Q / N=0.15), the solid hydrogenated nitrile rubber was continuously recovered at a rate of 48 kg / hr by carrying out coagulation, washing, dehydration and drying of the hydrogenated nitrile rubber latex (L1) in the same manner as in Example 1. In addition, the recovered hydrogenated nitrile rubber was used to perform evaluation in the same manner as in Example 1, and a rubber composition was prepared and evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0125] [Comparative Example 1] The hydrogenated nitrile rubber latex (L1) obtained in Production Example 1 was used as it was without compounding a hindered phenol-based antiaging agent, and adjusted to pH = 3.6 using an aqueous sulfuric acid solution (solid content concentration: 13.5 wt%). The hydrogenated nitrile rubber latex (L1) was coagulated, washed, dehydrated and dried in the same manner as in Example 1, and solid hydrogenated nitrile rubber was continuously recovered at a rate of 48 kg / hr. The recovered hydrogenated nitrile rubber was used to perform evaluation in the same manner as in Example 1, and a rubber composition was prepared and evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0126] [Comparative Example 2] To the hydrogenated nitrile rubber latex (L1) obtained in Production Example 1, 0.6 parts of 2,5-di-t-amylhydroquinone (molecular weight: 250.4) as a polyphenol-based antiaging agent was added in an emulsion state dispersed in 1.25 parts of a 20% by weight aqueous solution of sodium alkylbenzenesulfonate relative to 100 parts by weight of the solid content in the latex, thereby preparing a latex (solid content concentration: 13.5% by weight) to which a polyphenol-based antiaging agent was added. Then, the latex to which the polyphenol-based antioxidant was added was used, and the pH was adjusted to 3.6 (solid content concentration: 13.5% by weight) using an aqueous sulfuric acid solution. The supply rate of the hydrogenated nitrile rubber latex was changed to 326 kg / hr (44 kg / hr in terms of hydrogenated nitrile rubber), and the screw rotation speed of the extruder 1 was changed to 200 pm (i.e., Q / N=0.22). Except for this, the hydrogenated nitrile rubber latex (L1) was coagulated, washed, dehydrated, and dried in the same manner as in Example 1. Solid hydrogenated nitrile rubber was continuously recovered at a rate of 42 kg / hr. The recovered hydrogenated nitrile rubber was used to perform evaluation in the same manner as in Example 1, and a rubber composition was prepared and evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0127] [Comparative Example 3] A latex (solid content concentration: 13.5% by weight) containing a polyphenol-based antioxidant was obtained in the same manner as in Comparative Example 2, except that 2,5-di-t-butylhydroquinone was added as a polyphenol-based antioxidant to the hydrogenated nitrile rubber latex (L1) obtained in Production Example 1, instead of in the form of an emulsion. The obtained latex containing a polyphenol-based antioxidant was adjusted to pH=3.6 using an aqueous sulfuric acid solution (solid content concentration: 13.5% by weight), and then the hydrogenated nitrile rubber latex (L1) was coagulated, washed, dehydrated, and dried in the same manner as in Comparative Example 2, to continuously recover solid hydrogenated nitrile rubber at a rate of 42 kg / hr. The recovered hydrogenated nitrile rubber was used to perform evaluation in the same manner as in Example 1, and a rubber composition was prepared and evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0128] [Comparative Example 4] A latex (solid content concentration: 13.5% by weight) containing a hindered phenol-based antioxidant was obtained in the same manner as in Example 1, except that an emulsion of 4,6-bis(octylthiomethyl)-o-cresol prepared in the same manner as in Example 1 was added to the hydrogenated nitrile rubber latex (L1) obtained in Production Example 1 so that the amount of 4,6-bis(octylthiomethyl)-o-cresol added as a hindered phenol-based antioxidant was 4.0 parts relative to 100 parts of solid content in the latex. Then, using the obtained latex to which the hindered phenol-based antioxidant was added, the pH was adjusted to 3.6 using an aqueous sulfuric acid solution (solid content concentration: 13.5% by weight), and the screw rotation speed of the extruder 1 was changed to 200 rpm (i.e., Q / N=0.25). Except for this, the latex (L1) of the hydrogenated nitrile rubber was coagulated, washed, dehydrated, and dried in the same manner as in Example 1, and the solid hydrogenated nitrile rubber was continuously recovered at a rate of 48 kg / hr. In addition, the recovered hydrogenated nitrile rubber was used to perform evaluation in the same manner as in Example 1, and a rubber composition was prepared and evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0129] [Comparative Example 5] To the hydrogenated nitrile rubber latex (L1) obtained in Production Example 1, 0.6 parts of 2,6-di-t-butyl-4-methylphenol (manufactured by Ouchi Shinko Chemical Industry Co., Ltd., product name "Nocrac 200", molecular weight: 220.4) as a monophenol-based antiaging agent was added as it was, relative to 100 parts by weight of solid content in the latex, to prepare a latex (solid content concentration: 13.5% by weight) to which a monophenol-based antiaging agent was added. Then, using the obtained latex to which a monophenol-based antiaging agent was added, pH was adjusted to 3.6 using an aqueous sulfuric acid solution (solid content concentration: 13.5% by weight), and the screw rotation speed of the extruder 1 was changed to 200 rpm (i.e., Q / N=0.25), and the solid hydrogenated nitrile rubber was continuously recovered at a rate of 48 kg / hr by carrying out coagulation, washing, dehydration and drying of the hydrogenated nitrile rubber latex (L1) in the same manner as in Example 1. In addition, the recovered hydrogenated nitrile rubber was used to perform evaluation in the same manner as in Example 1, and a rubber composition was prepared and evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0130] [Table 1]
[0131] As shown in Table 1, by adding 0.1 to 3 parts of a hindered phenol-based antioxidant having a molecular weight of 300 to 3000 to 100 parts of hydrogenated nitrile rubber in the latex to the hydrogenated nitrile rubber latex and feeding the mixture to an extruder, when a solid hydrogenated nitrile rubber is recovered from the hydrogenated nitrile rubber latex, it is possible to suppress the fouling of the extruder, and when the rubber composition is made into a rubber composition, the Mooney viscosity (compound Mooney) is low and the processability is excellent, and furthermore, it is possible to effectively suppress the fouling of the mold during molding and crosslinking (Examples 1 to 7).
[0132] On the other hand, when the hydrogenated nitrile rubber latex was fed to the extruder without adding a hindered phenol-based antioxidant having a molecular weight of 300 to 3000, the rubber composition had a high Mooney viscosity (compound Mooney) and was poor in processability (Comparative Example 1). When an antioxidant other than the hindered phenol-based antioxidant having a molecular weight of 300 to 3000 was used instead of the hindered phenol-based antioxidant having a molecular weight of 300 to 3000, the extruder was soiled, and the productivity was poor (Comparative Examples 2, 3, and 5). Furthermore, when the amount of the hindered phenol-based antioxidant having a molecular weight of 300 to 3000 used was too large, mold staining occurred during molding and crosslinking, resulting in poor productivity (Comparative Example 4).
Claims
1. A method for producing nitrile rubber, comprising the steps of continuously supplying nitrile rubber latex and a coagulant to an extruder having a screw rotatably disposed inside a barrel, and recovering nitrile rubber from the nitrile rubber latex, comprising the steps of: the nitrile rubber latex is supplied to the extruder in a state in which the nitrile rubber latex contains a hindered phenol-based antioxidant having a molecular weight of 300 to 3000 in an amount of 0.1 to 3 parts by weight per 100 parts by weight of the nitrile rubber, A method for producing nitrile rubber, comprising the steps of: adding the hindered phenol-based antioxidant to the nitrile rubber latex in an emulsion state.
2. The method for producing nitrile rubber according to claim 1, wherein the maximum chemiluminescence intensity of the nitrile rubber discharged from the extruder and recovered from the nitrile rubber latex, as measured in accordance with JIS K7351:2018, is 2,000 to 25,000 counts / second.
3. The method for producing nitrile rubber according to claim 1 or 2, wherein the nitrile rubber contains 5 to 60% by weight of α,β-ethylenically unsaturated nitrile monomer units and has an iodine value of 120 or less.
4. The method for producing nitrile rubber according to any one of claims 1 to 3, wherein the ratio Q / N [kg / (hr·rpm)] of the supply rate Q [kg / hr] of the nitrile rubber to the extruder and the rotation speed N [rpm] of the screw of the extruder is 0.22 kg / (hr·rpm) or less.
Citation Information
Patent Citations
Maleimide-modified ABS resin composition
JP1997216981A
Resin pellet mixture for connector, and method of producing the same
JP2001247754A
Rubber composition
JP2002155172A
New elastomer composite, method and apparatus
JP2009041026A
Method for continuously manufacturing rubber
JP2011012142A
Cited By
Resin composition, molding, and method for manufacturing them
JP2023089548A